AARRE presenting the world through souvenirs. (25th November 2008) - Malmberg, Viljo; Sutela, Jenna
AARRE is a concept for a web service (an online exhibition) and its tangible presentation: an exhibition at Helina Rautavaara Museum. It was designed and developed at the University of Art and Design Helsinki by Viljo Malmberg and Jenna Sutela. The concept builds on extending the physical museum experience to involve also virtual aspects, creating dialogue between the museum visitors and the museum as well as enabling museum visitors to participate in the production of museum content.